Machine learning and data analytics for predicting, managing, and monitoring disease - Roy, Manikant; Gupta, Lovi Raj 196X- (IGI Global, Publisher of Timely Knowledge, 2021)
"This book provides the recent various theoretical frameworks, empirical research and application of advanced analytics methods for disease detection, pandemic management, disease prediction etc. using the data analysis methods and their usages for taking timely decisions for prevention of such spread of pandemic and how people in government, society and administer can use these insights for overall management" - Provided by publisher
Includes bibliographical references and index
Keywords: Epidemiology / Data processing; Epidemics / Mathematical models; Machine learning; Artificial intelligence / Medical applications; Artificial intelligence; Medical applications; Epidemics; Mathematical models; Epidemiology; Data processing; Aufsatzsammlung